Mitigasi Konflik Manusia-Buaya Muara di Desa Kayu Besi dan Bukit Layang, Kabupaten Bangka - Randi Syafutra; Ririn Apriyani; Heri; Lilis Karsina; Nur Azizah Nawang Wulan (Cv. Utility Project Solution, 2023)
This Community Service (CS) project was conducted due to the high intensity of saltwater crocodile attacks on the people of Kayu Besi and Bukit Layang Villages, Bangka Regency, Bangka Belitung Islands Province. This project used three methods in stages, i.e.: (1) Unstructured Interview, (2) Focus Group Discussion (FGD), and (3) Socialization. The interview results showed that the people in both villages had lack of knowledge and negative attitude and perception toward saltwater crocodile. The FGD results showed that the people in both villages: (1) asked for socialization on mitigation conflict between human-saltwater crocodile, (2) frequently disposed carcasses in the watersheds in both villages, and (3) asked for solutions to anticipate casualties due to the human-saltwater crocodile conflict. The socialization on the mitigation of human-saltwater crocodile conflict was held immediately after the FGD. The unfinished follow-up of the FGD results will be held in the next project. In the end, this CS project offered impacts on increasing knowledge and improving attitude and perception of the people towards saltwater crocodile in both villages.